Analyzing The Impact Of Gender And School Background On Islamic Religious Education Learning Outcomes - Ikromi, Shoutika Nawadya; Al Ayyubi, Ibnu Imam; Nurhikmah; Annastasya, Tiara; Rahmawati, Siti (Journal of Education and Learning Sciences, 2025)
Islamic Religious Education (PAI) plays a crucial role in shaping students' moral and religious understanding. However, the extent to which external demographic factors, such as gender and school background, influence PAI learning outcomes remains debatable. This study aims to analyze the impact of gender and school background on students' PAI learning outcomes. A quantitative research approach was employed, utilizing descriptive statistical analysis and Two-Way ANOVA to examine significant differences based on the studied variables. The findings indicate that neither gender nor school background significantly affects students' PAI learning outcomes. The normality test confirmed that the data followed a normal distribution, while the homogeneity test showed that the data did not have equal variance. The Two-Way ANOVA results further revealed no significant interaction effect between gender and school background on learning outcomes. These results suggest that internal factors, such as teaching methods and student engagement, have a more substantial influence on PAI learning effectiveness than demographic variables. Therefore, educators should focus on developing innovative and adaptive learning strategies to enhance PAI learning outcomes, rather than relying on external factors like gender or school environment.